Glass fiber reinforced nylon composite material and preparation method thereof
By modifying the combination of glass fiber and nylon 6 and the self-lubricity of boron nitride, the tensile strength and elongation of break of nylon 6 composite materials are improved, and the problem of insufficient fatigue resistance in electric motorcycle applications is solved, and the problem of extended Service life and reduce replacement frequency.
Patent Information
- Application Number
- CN202411722015.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In electric motorcycle applications, nylon 6 composite materials have reduced elongation at break due to the rigidity of glass fibers and insufficient fatigue resistance, resulting in more frequent replacement of components, increasing user costs and maintenance difficulties.
Modified glass fibers are treated with silane coupling agent and dopamine-boron nitride surface modifier, combined with polyethylene glycol, antioxidant, lubricant and antistatic agent to prepare high tensile strength and elongation of break The fiberglass reinforced nylon composite material improves the fatigue resistance of the material by modifying the interface combination of glass fiber and nylon matrix and the self-lubricity of boron nitride.
The tensile strength and elongation of the composite material are significantly improved, which extends its service life under cyclic loads, ensures the fatigue resistance of the material, and reduces replacement frequency and maintenance costs.
Smart Images

Figure CN119192832A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a glass fiber reinforced nylon composite material and a preparation method thereof. Background Art
[0002] Polyamide-6, also known as nylon 6, is also called PA6. Its chemical and physical properties are very similar to those of nylon 66. It has a lower melting point and a wide processing temperature range. Its impact resistance and solvent resistance are better than nylon 66 plastic. In order to further improve the mechanical properties of nylon 6, various modifiers are often added.
[0003] Nylon 6 materials have a wide range of application scenarios, and different application scenarios have different performance requirements for nylon 6 materials. For example, when used on electric motorcycles, since the motorcycles are subject to various forces during operation, such as vibration and impact, materials with high mechanical strength are required to ensure the stability and safety of the structure. At this time, glass fiber, as a high-performance reinforcing material (modifier), is used in nylon 6 engineering plastics, which can significantly improve the mechanical properties of the composite materials, such as tensile strength and flexural strength.
[0004] However, because the rigidity of glass fiber makes it more difficult for composite materials to deform when subjected to force, the elongation at break of the composite material will decrease as the glass fiber content increases. During the use of electric motorcycles, the components will be subjected to repeated loads, which requires the material to have good fatigue resistance. Materials with low elongation at break are more likely to crack and expand under repeated loads, resulting in reduced fatigue resistance (fatigue life). This means that electric motorcycle parts need to be replaced more frequently, increasing the user's cost of use and maintenance difficulty. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a glass fiber reinforced nylon composite material and a preparation method thereof, which ensures that the tensile strength of the composite material is excellent while effectively avoiding the reduction of the elongation at break, so that the fatigue resistance of the composite material is guaranteed, thereby extending the service life.
[0006] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a glass fiber reinforced nylon composite material, comprising the following components by weight: 75-82 parts of nylon 6, 14-16 parts of modified glass fiber, 2-3 parts of polyethylene glycol, 0.4-0.7 parts of antioxidant, 0.6-1 parts of lubricant and 0.6-1 parts of antistatic agent;
[0007] The modified glass fiber is prepared by first treating the glass fiber with a silane coupling agent and then treating the glass fiber with a dopamine-boron nitride surface modifier.
[0008] Furthermore, the preparation method of the modified glass fiber is as follows:
[0009] A1. Soak 10 parts of glass fiber in 25-30 parts of 1.5-2% silane coupling agent ethanol solution by weight for 1.5-2 hours, filter out, and dry at 90-100℃ for 1-2 hours to obtain activated glass fiber.
[0010] A2. Soak the activated glass fiber obtained in A1 in 15-20 parts of dopamine-boron nitride surface modifier, ultrasonicate for 1-1.5 hours, and then rotary evaporate and dry to obtain modified glass fiber.
[0011] Furthermore, in A1, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0012] Further, in A2, the preparation method of the dopamine-boron nitride surface modifier is as follows:
[0013] B1. Dissolve 7.5 g of tris(hydroxymethyl)aminomethane in 6 L of deionized water, adjust the pH value to 8.5 with hydrochloric acid, then add 12.3 g of dopamine hydrochloride, and then add 3.1 g of hexagonal boron nitride powder, and perform ultrasonic treatment for 3 h to disperse the mixture evenly to obtain a mixed solution;
[0014] B2. The mixed solution was stirred and reacted at 60°C for 12 hours to promote the self-aggregation of dopamine molecules around the boron nitride nanosheets. After the reaction was completed, it was filtered and washed with deionized water for multiple times. The obtained product was vacuum dried at 60°C for 12 hours to obtain a gray-brown product, indicating that polydopamine had been successfully modified on the boron nitride nanosheets, that is, dopamine-boron nitride modified powder;
[0015] B3. Weigh 5 g of dopamine-boron nitride modified powder, put it into 90 mL of anhydrous ethanol, and disperse it ultrasonically for 1 hour until it is evenly dispersed to obtain the dopamine-boron nitride surface modifier.
[0016] Furthermore, the glass fiber is alkali-free glass fiber.
[0017] Furthermore, the antioxidant includes antioxidant 1010 and / or antioxidant 1098.
[0018] Furthermore, the lubricant includes any one of calcium stearate, stearic acid, and polyethylene wax, or a mixture of at least two of them.
[0019] Furthermore, the antistatic agent is a non-ionic antistatic agent.
[0020] In a second aspect, the present invention provides a method for preparing the above-mentioned glass fiber reinforced nylon composite material, comprising the following steps:
[0021] S1, adding nylon 6, modified glass fiber, polyethylene glycol, antioxidant, lubricant and antistatic agent into a mixer, and mixing evenly to obtain a mixture;
[0022] S2. Add the mixture obtained in S1 into a twin-screw extruder for extrusion granulation and drying to obtain a glass fiber reinforced nylon composite material.
[0023] Furthermore, in S2, the extrusion temperature of the twin-screw extruder is set to 215-265°C, and the screw speed is set to 200-350r / min.
[0024] This application has the following beneficial effects:
[0025] 1. There is a synergistic effect between the modified glass fiber of the present invention and polyethylene glycol, which can synergistically improve the tensile strength and elongation at break of the composite material, so that the tensile strength test data of the composite material is as high as 147.7MPa or more, and the elongation at break test data is as high as 40.1% or more, ensuring that the tensile strength of the composite material is excellent while also having a high elongation at break, so that the fatigue resistance of the composite material is guaranteed, thereby extending its service life under cyclic load.
[0026] 2. In the preparation of the modified glass fiber of the present invention, the glass fiber has the characteristics of high strength and high modulus. When it is added to the nylon matrix, it can improve the tensile strength of the composite material; but at the same time, the addition of glass fiber will limit the deformation ability of the nylon matrix, increase the rigidity of the composite material, and cause the elongation at break of the composite material to decrease.
[0027] Dopamine has strong adhesion and can interact with the active sites on the surface of glass fiber and the nylon matrix, thereby enhancing the interface bonding between glass fiber and nylon matrix, so as to more effectively transfer stress, reduce cracks caused by interface debonding, and enable the material to better disperse stress when subjected to stress, thereby improving the elongation at break. At the same time, the participation of boron nitride, on the one hand, because of its low friction coefficient and good self-lubrication, can reduce the stress concentration points inside the composite material, help reduce the initiation and expansion of cracks, and thus improve the elongation at break of the composite material; on the other hand, it can also improve the thermal properties of the composite material. Stable thermal properties mean that the composite material can better maintain its structural integrity when subjected to stress, indirectly improving the elongation at break of the composite material.
[0028] In summary, the modified glass fiber of the present invention can produce a synergistic effect to improve performance, significantly improve the tensile strength of the composite material, and effectively avoid a decrease in elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1, a comparative trend chart of tensile strength performance test data of composite materials obtained from Examples 1 to 6 of the present invention and Comparative Examples 1 to 5;
[0030] Figure 2 , a comparative trend chart of the elongation at break performance test data of the composite materials prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0033] Example 1: (1) Preparation of dopamine-boron nitride surface modifier, the preparation method is as follows:
[0034] B1. Dissolve 7.5 g of tris(hydroxymethyl)aminomethane in 6 L of deionized water, adjust the pH value to 8.5 with hydrochloric acid, then add 12.3 g of dopamine hydrochloride, and then add 3.1 g of hexagonal boron nitride powder, and disperse it evenly under 20 kHz ultrasound for 3 h to obtain a mixed solution.
[0035] Among them, tris(hydroxymethyl)aminomethane (purity ≥99%) was purchased from Wuhan Desheng Biochemical Technology Co., Ltd. Dopamine hydrochloride was purchased from Guangzhou Hexue Biotechnology Co., Ltd. Hexagonal boron nitride powder (content ≥98.5%, C model - particle size 8-12μm) was purchased from Tianyuan Aerospace Materials (Yingkou) Technology Co., Ltd.
[0036] B2. The mixed solution was stirred at 60°C at a stirring speed of 140 r / min for 12 hours to promote the self-aggregation of dopamine molecules around the boron nitride nanosheets. After the reaction was completed, it was filtered and washed three times with deionized water. The product was vacuum dried at 60°C for 12 hours to obtain a gray-brown product, indicating that polydopamine had been successfully modified on the boron nitride nanosheets, namely, dopamine-boron nitride modified powder.
[0037] B3. Weigh 5 g of dopamine-boron nitride modified powder, put it into 90 mL of anhydrous ethanol, and disperse it by ultrasonic at 50 kHz for 1 hour until it is evenly dispersed to obtain the dopamine-boron nitride surface modifier.
[0038] (2) Preparing modified glass fiber, the preparation method is as follows:
[0039] A1. Soak 10 parts of glass fiber in 28 parts of 1.8% γ-aminopropyltriethoxysilane ethanol solution by weight for 1.8 hours, filter out, and dry at 95°C for 1.5 hours to obtain activated glass fiber.
[0040] Among them, the glass fiber is alkali-free glass fiber (3mm, grade A), which is purchased from Lingshou County Shuolong Mineral Products Processing Plant. γ-aminopropyltriethoxysilane (purity 98%) is purchased from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.
[0041] A2. Based on the same standard weight proportions, the activated glass fiber obtained in A1 was immersed in 18 parts of dopamine-boron nitride surface modifier, subjected to 40kHz ultrasound for 1.2 hours, and then subjected to rotary evaporation and drying to obtain the modified glass fiber.
[0042] (3) A method for preparing a glass fiber reinforced nylon composite material, comprising the following steps:
[0043] S1. By weight, 80 parts of nylon 6, 15 parts of modified glass fiber, 2.8 parts of polyethylene glycol, 0.6 parts of antioxidant, 0.8 parts of lubricant and 0.8 parts of antistatic agent are added into a mixer and mixed evenly to obtain a mixture. In the mixture, the mass fraction of nylon 6 is 80%, and the mass fraction of modified glass fiber is 15%.
[0044] Among them, nylon 6 (Germany Lanxess B30S food grade) was purchased from Shanghai Younoshi Plastic Technology Co., Ltd. Polyethylene glycol PEG-2000 was purchased from Tianjin Zhonghe Shengtai Chemical Co., Ltd. The antioxidant is antioxidant 1010 (superior grade), purchased from Dongguan Dinghai Plastic Chemical Co., Ltd. The lubricant is calcium stearate (superior grade), purchased from Dongguan Shanyi Plastic Co., Ltd. The antistatic agent is non-ionic antistatic agent T-92, purchased from Jinan Hexin Chemical Co., Ltd.
[0045] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0046] Example 2: The difference between this example and Example 1 is that: (2) the modified glass fiber is prepared, and the preparation method thereof is as follows:
[0047] A1. Soak 10 parts of glass fiber in 25 parts of 1.5% γ-aminopropyltriethoxysilane ethanol solution by weight for 1.5 hours, filter out, and dry at 90°C for 1 hour to obtain activated glass fiber.
[0048] A2. Soak the activated glass fiber obtained in A1 in 15 parts of dopamine-boron nitride surface modifier, ultrasonicate at 40kHz for 1 hour, and then rotary evaporate and dry to obtain modified glass fiber.
[0049] Example 3: The difference between this example and Example 1 is that: (2) the modified glass fiber is prepared, and the preparation method thereof is as follows:
[0050] A1. Soak 10 parts of glass fiber in 30 parts of 2% γ-aminopropyltriethoxysilane ethanol solution by weight for 2 hours, filter out, and dry at 100°C for 2 hours to obtain activated glass fiber.
[0051] A2. Soak the activated glass fiber obtained in A1 in 20 parts of dopamine-boron nitride surface modifier, ultrasonicate at 40kHz for 1.5h, and then rotary evaporate and dry to obtain modified glass fiber.
[0052] Example 4: The difference between this example and Example 1 is that: (3) A method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0053] S1. Add 75 parts of nylon 6, 14 parts of modified glass fiber, 3 parts of polyethylene glycol, 0.4 parts of antioxidant, 0.6 parts of lubricant and 0.6 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0054] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 260r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0055] Example 5: The difference between this example and Example 1 is that: (3) A method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0056] S1. Add 82 parts of nylon 6, 16 parts of modified glass fiber, 3 parts of polyethylene glycol, 0.7 parts of antioxidant, 1 part of lubricant and 1 part of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0057] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 320r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0058] Example 6: The difference between this example and Example 1 is that: (3) A method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0059] S1. Add 78 parts of nylon 6, 15 parts of modified glass fiber, 2.5 parts of polyethylene glycol, 0.6 parts of antioxidant, 0.6 parts of lubricant and 0.8 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0060] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 320r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0061] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of the glass fiber reinforced nylon composite material, the modified glass fiber and polyethylene glycol are deleted.
[0062] Specifically, a method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0063] S1. Add 80 parts of nylon 6, 0.6 parts of antioxidant, 0.8 parts of lubricant and 0.8 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0064] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0065] Comparative Example 2: The difference between this comparative example and Example 1 is that in the preparation of the glass fiber reinforced nylon composite material, polyethylene glycol is deleted and the modified glass fiber is replaced by glass fiber.
[0066] Specifically, a method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0067] S1. Add 80 parts of nylon 6, 15 parts of glass fiber, 0.6 parts of antioxidant, 0.8 parts of lubricant and 0.8 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0068] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0069] Comparative Example 3: The difference between this comparative example and Example 1 is that polyethylene glycol is deleted in the preparation of the glass fiber reinforced nylon composite material.
[0070] Specifically, a method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0071] S1. Add 80 parts of nylon 6, 15 parts of modified glass fiber, 0.6 parts of antioxidant, 0.8 parts of lubricant and 0.8 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0072] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0073] Comparative Example 4: The difference between this comparative example and Example 1 is that in the preparation of the glass fiber reinforced nylon composite material, the modified glass fiber is replaced by glass fiber.
[0074] Specifically, a method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0075] S1. Add 80 parts of nylon 6, 15 parts of glass fiber, 2.8 parts of polyethylene glycol, 0.6 parts of antioxidant, 0.8 parts of lubricant and 0.8 parts of antistatic agent into a mixer by weight, mix well to obtain a mixture.
[0076] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0077] Comparative Example 5: The difference between this comparative example and Example 1 is that the antistatic agent is deleted in the preparation of the glass fiber reinforced nylon composite material.
[0078] Specifically, a method for preparing a glass fiber reinforced nylon composite material comprises the following steps:
[0079] S1. Add 80 parts of nylon 6, 15 parts of modified glass fiber, 2.8 parts of polyethylene glycol, 0.6 parts of antioxidant and 0.8 parts of lubricant into a mixer by weight, mix well to obtain a mixture.
[0080] S2, set the extrusion temperature of the twin-screw extruder to 215-265°C, the screw speed to 300r / min, add the mixture obtained in S1 to the twin-screw extruder for extrusion granulation, and dry to obtain a glass fiber reinforced nylon composite material. Specifically, the nine zones of the twin-screw extruder from the feeding section to the die are set to 215°C, 225°C, 235°C, 250°C, 265°C, 265°C, 250°C, 230°C, and 220°C.
[0081] Test example: Test object: Example 1-Example 6 and Comparative Example 1-Comparative Example 5.
[0082] Test items: 1. Tensile strength; 2. Elongation at break.
[0083] Test method / basis: The performance tests of tensile strength and elongation at break are all based on GB / T1040-92.
[0084] Test results: See Table 1.
[0085] Table 1. Test data of the experimental example
[0086] Tensile strength / MPa Elongation at break / % Example 1 148.2 40.3 Example 2 149.3 41.1 Example 3 147.7 40.1 Example 4 148.8 40.7 Example 5 149.1 40.4 Example 6 148.5 40.8 Comparative Example 1 88.7 40.5 Comparative Example 2 142.5 31.6 Comparative Example 3 138.8 38.6 Comparative Example 4 145.4 31.9 Comparative Example 5 143.7 38.1
[0087] Result analysis: Analyze Example 1-Example 6 and combine the data in Table 1 and Figure 1-Figure 2 It can be seen that the tensile strength test data of the composite material prepared by the present invention is as high as 147.7MPa or more, and the elongation at break test data is as high as 40.1% or more. This shows that the composite material prepared by the present invention has excellent tensile strength and high elongation at break, so that the fatigue resistance of the composite material is guaranteed, thereby extending its service life under cyclic load.
[0088] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1-Figure 2By comparing Comparative Example 1 and Comparative Example 2, it can be seen that compared with Comparative Example 1, glass fiber is added to the raw material components of Comparative Example 2, and the tensile strength of the composite material obtained is significantly improved, from 88.7MPa (Comparative Example 1) to 142.5MPa (Comparative Example 2), while the elongation at break is significantly reduced, from 40.5% (Comparative Example 1) to 31.6% (Comparative Example 2). This shows that the addition of glass fiber can significantly improve the tensile strength of the obtained nylon composite material, but at the same time, it will also cause the elongation at break of the obtained nylon composite material to be significantly reduced.
[0089] From the comparison between Comparative Example 2 and Comparative Example 3, it can be seen that compared with Comparative Example 2, Comparative Example 3 uses the glass fiber as the modified glass fiber of the present invention, and the tensile strength of the composite material obtained is slightly reduced from 142.5MPa (Comparative Example 2) to 138.8MPa (Comparative Example 3), while the elongation at break is significantly improved from 31.6% (Comparative Example 2) to 38.6% (Comparative Example 3). This shows that using the glass fiber as the modified glass fiber of the present invention can significantly improve the elongation at break of the obtained nylon composite material, but at the same time, it will also cause the tensile strength of the obtained nylon composite material to be slightly reduced.
[0090] From the comparison between Comparative Example 2 and Comparative Example 4, it can be seen that compared with Comparative Example 2, in the presence of glass fiber, polyethylene glycol is added to the raw material components of Comparative Example 4, and the tensile strength of the composite material obtained is slightly improved from 142.5MPa (Comparative Example 2) to 145.4MPa (Comparative Example 4), and the elongation at break is slightly improved (from the data comparison alone, the improvement is very small, and it can also be considered that there is almost no change), from 31.6% (Comparative Example 2) to 31.9% (Comparative Example 4). It shows that in the presence of glass fiber, the addition of polyethylene glycol can slightly improve the tensile strength and elongation at break of the nylon composite material.
[0091] By comparing Comparative Example 3 and Example 1, it can be seen that compared with Comparative Example 3, under the premise of the presence of the modified glass fiber of the present invention, polyethylene glycol is added to the raw material components of Example 1, and as a result, the tensile strength of the composite material obtained is increased from 138.8 MPa (Comparative Example 3) to 148.2 MPa (Example 1), and the elongation at break is increased from 38.6% (Comparative Example 3) to 40.3% (Example 1); the improvement in both properties is significantly greater than the improvement in Comparative Example 4 compared to Comparative Example 2, indicating that there is a synergistic effect between the modified glass fiber of the present invention and polyethylene glycol, which can synergistically improve the tensile strength and elongation at break of the composite material obtained.
[0092] By comparing Comparative Example 5 and Example 1, it can be seen that compared with Comparative Example 5, the nonionic antistatic agent T-92 is added to the raw material components of Example 1. As a result, the tensile strength of the composite material obtained is increased from 143.7MPa (Comparative Example 5) to 148.2MPa (Example 1), and the elongation at break is increased from 38.1% (Comparative Example 5) to 40.3% (Example 1); This shows that the addition of the nonionic antistatic agent T-92 can improve the tensile strength and elongation at break of the obtained nylon composite material.
[0093] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0094] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A glass fiber reinforced nylon composite material, characterized in that: The composition comprises the following components by weight: 75-82 parts of nylon 6, 14-16 parts of modified glass fiber, 2-3 parts of polyethylene glycol, 0.4-0.7 parts of antioxidant, 0.6-1 parts of lubricant and 0.6-1 parts of antistatic agent; The modified glass fiber is prepared by first treating the glass fiber with a silane coupling agent and then treating the glass fiber with a dopamine-boron nitride surface modifier.
2. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: A1. Soak 10 parts of glass fiber in 25-30 parts of 1.5-2% silane coupling agent ethanol solution by weight for 1.5-2 hours, filter out, and dry at 90-100℃ for 1-2 hours to obtain activated glass fiber. A2. Soak the activated glass fiber obtained in A1 in 15-20 parts of dopamine-boron nitride surface modifier, ultrasonicate for 1-1.5 hours, and then rotary evaporate and dry to obtain modified glass fiber.
3. The glass fiber reinforced nylon composite material according to claim 2, characterized in that: In A1, the silane coupling agent is γ-aminopropyltriethoxysilane.
4. The glass fiber reinforced nylon composite material according to claim 2, characterized in that: In A2, the preparation method of the dopamine-boron nitride surface modifier is as follows: B1, dissolve 7.5g of tris(hydroxymethyl)aminomethane in 6L of deionized water, adjust the pH value to 8.5 with hydrochloric acid, then add 12.3g of dopamine hydrochloride, and then add 3.1g of hexagonal boron nitride powder, and ultrasonicate for 3h to obtain a mixed solution; B2, stirring the mixed solution obtained in B1 at 60°C for 10 hours, then filtering and washing with deionized water for multiple times, and vacuum drying the obtained product at 60°C for 8 hours to obtain dopamine-boron nitride modified powder; B3. Weigh 5 g of dopamine-boron nitride modified powder, put it into 90 mL of anhydrous ethanol, and disperse it ultrasonically for 1 hour until it is evenly dispersed to obtain the dopamine-boron nitride surface modifier.
5. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber.
6. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The antioxidant includes antioxidant 1010 and / or antioxidant 1098.
7. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The lubricant includes any one of calcium stearate, stearic acid, and polyethylene wax, or a mixture of at least two of them.
8. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The antistatic agent is a nonionic antistatic agent.
9. A method for preparing a glass fiber reinforced nylon composite material according to any one of claims 1 to 8, characterized in that: The steps include: S1, adding nylon 6, modified glass fiber, polyethylene glycol, antioxidant, lubricant and antistatic agent into a mixer, and mixing evenly to obtain a mixture; S2. Add the mixture obtained in S1 into a twin-screw extruder for extrusion granulation and drying to obtain a glass fiber reinforced nylon composite material.
10. The method for preparing a glass fiber reinforced nylon composite material according to claim 9, characterized in that: In S2, the extrusion temperature of the twin-screw extruder is set to 215-265°C and the screw speed is set to 200-350r / min.
Citation Information
Patent Citations
Reinforced flame-retardant PA6 (polyamide) / ABS (acrylonitrile-butadiene-styrene) composite material and preparation method thereof
CN103183959A
Polyamide composition and method of improving wear resistance of polyamide composition
CN111320866A
Polyamide composite material capable of being subjected to gas-assisted molding
CN112552676A
Mixed olefin grafted microsphere reinforced flame-retardant nylon 6 composition and preparation method thereof
CN112708261A
Low-warpage easy-to-weld nylon composite material and preparation method thereof
CN116003999A
Cited By
High-performance ethylene propylene diene monomer foaming material and preparation method thereof
CN119859355A
A high-performance EPDM rubber foam material and its preparation method
CN119859355B
High-wear-resistance modified nylon-based material and preparation method thereof
CN120349613A
High-thermal-conductivity glass fiber reinforced polypropylene composite material and preparation method thereof
CN121226912A
Glass fiber reinforced nylon 6 composite material and preparation method thereof
CN122483559A